Bioactive Peptides from Indonesian High-Protein Fermented Foods: A Promising Source of Functional Compounds - Kurnianto, Muhammad Alfid; Aulia, Salma Shafrina; Septiana, Siska; Syahbanu, Fathma; Munarko, Hadi; Tinh, Nguyen Thi Thanh; Chasanah, Ekowati; Rini, Dina Mustika (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research Fermentation improves the biological function of proteins. Bioactive peptides increase after fermentation. Indonesia has many unexplored sources of bioactive peptides in fermented food. Indonesian high-protein fermented foods have high bioactivity potential. Research is needed on the bioactivity of Indonesian bioactive peptides sources for broader health implications.     Abstract Bioactive peptides (BPs) are short protein fragments with significant physiological functions, including antioxidant, antihypertensive, antimicrobial, and antidiabetic activities. These compounds are commonly released during fermentation, making high-protein fermented foods (HPFF) a promising source of natural health-promoting agents. Indonesia, with its rich biodiversity and long-standing tradition of fermentation, offers a unique variety of traditional HPFF. However, the potential of these indigenous products as BP sources remains underexplored and poorly represented in the global literature. This review aims to examine Indonesian traditional HPFF as a source of BPs, categorize them based on raw material, and highlight their functional and health-related properties. A literature review was conducted using publications from Scopus, PubMed, ProQuest, Google Scholar, and SINTA (2000–2023). The search applied Boolean strategies and the PEO (Population, Exposure, Outcome) framework to identify relevant studies on fermented foods, bioactive peptides, and their biological activities. Indonesian HPFF including tempeh, rusip, dangke, pekasam, and cangkuk contain BPs with diverse bioactivities. Tempeh shows antidiabetic and antihypertensive potential; rusip exhibits antioxidant and cholesterol-lowering effects; dangke and cangkuk demonstrate antimicrobial and ACE-inhibitory activities. These functional properties are influenced by substrate type (e.g., legumes, fish, milk), microbial composition (lactic acid bacteria, Bacillus spp., yeasts), and fermentation conditions. Notably, certain Indonesian HPFF exhibit multi-functional peptides with synergistic health effects, suggesting significant therapeutic promise. This review bridges a critical knowledge gap by consolidating evidence on BPs from Indonesian HPFF. It provides a foundation for future investigations into peptide bioactivity, supports functional food innovation, and highlights the global relevance of Indonesia’s fermentation heritage in health science and sustainable nutrition.